Foreign market entry with circular business models: a customer-centric approach - Yurdaanik Eskiyerli, Devrim; Ewertz, Simon (Frontiers in Sustainability, 2024)
Circular business models have been developed in recent years, driven by concerns over environmental sustainability. The circular business models are initially tested domestically, but businesses may aspire to expand internationally with it. However, entering foreign markets with circular business models, which include novel products and innovative services, may be challenging. Moreover, generalized foreign market entry criteria for circular business models are lacking. This in-depth case study utilized a mixed-method approach to shed light on the tactical adaptations businesses need to make in their circular business model when entering foreign markets while also ensuring economic competitiveness. The case includes foreign market entry with a circular ”service” business model; therefore, we emphasized the customer side of the business model canvas related to customer relationships. In our conclusion, we identify five tactical adaptations, namely implementing a co-creation tool for customization, offering tangible customized benefits, increasing investment in social media marketing, utilizing start up incubators/accelerators/co-working spaces as a marketing channel and offering adjustable contract lengths. Foreign markets with circular business models and involving the value network partners of the business are also expected to expand the positive externalities of circular economy internationally.